Is testosterone responsible for athletic success in female athletes? - Ahmetov, I. I.; Roos, T. R.; Stepanova, A. A.; Biktagirova, E. M.; Semenova, E. A.; Shchuplova, I. S.; Bets, L. V. (Research Institute for Sport and Exercise Sciences, Liverpool John Moores University, Liverpool, United Kingdom, 2019)
The aim of this study is to determine the interrelationship between the resting serum testosterone (T) levels (an inherited trait) of female athletes from different types of sporting events and their athletic success. The study involves 599 Russian international-level female athletes (95 highly elite, 190 elite, and 314 sub-elite) and 298 age-matched female controls. All subjects were age 16-35 years old and to the best of our knowledge have always tested negative for performance enhancing substances. The athlete cohort was stratified into four groups according to event duration, distance, and type of activity: 1) endurance athletes, 2) athletes with mixed activity, 3) speed/strength athletes, and 4) sprinters. Athletic success was measured by determining the level of achievement of each athlete. The mean (SD) T levels of athletes and controls were 1.65 (0.87) and 1.76 (0.6) nmol/L (P=0.057) with ranges of 0.08-5.80 and 0.38-2.83 nmol/L in athletes and controls, respectively. No significant differences in T levels were found between different groups of athletes. T levels were positively correlated (r=0.62, P<0.0001) with athletic success in sprinters (runners, cyclists, kayakers, speed skaters, swimmers). Moreover, none of the sub-elite sprinters had T > 1.9 nmol/L, while 50% of elite and highly elite sprinters had T > 1.9 nmol/L (95% CI: 2.562-862.34; OR=47.0; P<0.0001). We do not observe the benefits of having high T levels for success in other groups of athletes. Conversely, highly elite middle-distance (P=0.235) and mixed activity athletes (P=0.096) tended to have lower T levels than less successful athletes. Our data suggest that the measurement of the serum T levels significantly correlates with athletic success in sprinters but not other types of athletes and in the future may be useful in the prediction of sprinting ability.